Five in situ observations of live oarfish Regalecus glesne (Regalecidae) by remotely operated vehicles in the oceanic waters of the northern Gulf of Mexico. Issue 1 (5th June 2013) - Benfield, M. C.; Cook, S.; Sharuga, S.; Valentine, M. M.
Abstract : As part of the SERPENT Project, five observations of apparently healthy oarfish Regalecus glesne by remotely operated vehicles are reported from the northern Gulf of Mexico. Regalecus glesne were observed between 2008 and 2011 at depths from within the epipelagic and mesopelagic zones. These observations include the deepest verified record of R. glesne (463–492 m) and the first record of an arthropod ectoparasite (isopod).